PERAN LAYANAN ONLINE FOOD DELIVERY BAGI MAHASISWA BISNIS DIGITAL UIN K.H. ABDURRAHMAN WAHID PEKALONGAN - Adriansah, Noval; Rozaq, Maulana Fathur; Pratama, Versiandika Yudha (Politeknik Ubaya, 2026)
This study aims to examine student behavior in using online food delivery services through the lens of the Theory of Planned Behavior (TPB). The research focuses on understanding how attitudes, subjective norms, and perceived behavioral control shape user intentions and actual behaviors in engaging with app-based food delivery platforms. This study employed a qualitative method, collecting data through in-depth interviews with ten respondents. The data were analyzed using reduction, data display, and conclusion drawing techniques to identify behavioral patterns and the underlying factors influencing the use of online food delivery services. The findings indicate that positive attitudes toward convenience, speed, and efficiency serve as key drivers encouraging the adoption of food delivery services. Subjective norms also play a significant role, as the use of such services has become a common practice within students’ academic and social environments. Perceived behavioral control is reflected in the ease of navigating applications and the availability of multiple digital payment options, although financial constraints—particularly delivery fees—act as notable barriers that limit the realization of actual behavior. Overall, the study highlights that the use of online food delivery services among students is shaped by the interaction of all three TPB components, with promotional offers emerging as a strong stimulus influencing user intentions.